Kontribusi Fasilitas dan Disiplin Belajar Terhadap Hasil Belajar Siswa dalam Pembelajaran IPS - Lili Dianah (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
The research was based on the low value of social studies learning in Public Junior High School in West Bandung regency. The average value of KKM (Minimum Achievement Criteria), that was 66.08 which was still below the value set by LPMP (Education Quality Assurance Institution) that was at least 75. The research was conducted to find out the contribution of facility and learning discipline toward student learning result in social studies learning. This research used quantitative approach and Survey method (explanatory research). Analysis of learning result throughed average of student test results, and analysis of dicipline and learning facilities used questionnaire. The population students were 4231 students from 13 schools that classified SSN (National School Standar) in West Bandung regency. For research samples, there were 256 students from 7 schools. The sampling used Stratified Random Sampling. The results showed that learning facilities contributed to student learning result was 0.191 or 3.6%. The discipline of learning contributed to student learning outcomes was 0.353 or 12.5%. From the results of the study could be concluded that the facilities and discipline of student learning had a significant contribution to student learning result. Therefore the completeness of the facilities and the level of discipline students had to be improved and got attention more.